Risk Detection and Prevention of Degenerative Disease of The Elderly After COVID-19 Pandemic in Kutai Kartanegara Regency - Siswanto, Siswanto; Pakki, Irfansyah Baharuddin; Naim, Tanti Asrianti; Al Ahmadi, Khumairotul Zahroh; Dzikri, Akhmad (Journal of Mestika Nusantara Satu Community Services, 2024)
Aging or more commonly known as elderly is a natural process that cannot be avoided where in this condition, physiological and psychological function begin to decline and become vulnerable to diseases. Based on aggregate population data in 2020, it was estimated that the number of elderly will be around 28.8 million or 11.34% of the population in Indonesia, of which 236,844 elderly are in East Kalimantan Province. Based on Central Bureau of Statistics of East Kalimantan Province, the proportion of elderly in Kutai Kartanegara District in 2023 were 6.83%. Degenerative disease in the elderly can weaken the body’s immune system, making them susceptible to other diseases. The main causes of degenerative diseases are unhealthy lifestyle such as smoking habit, irregular eating pattern, lack of physical activity, exposure to environmental pollution and so on. In 2022, around 6.7% or 2.980 of elderly will have impairment of independence. The aim of this activity was to provide education to the elderly about healthy lifestyles so that can reduce morbidity and mortality rates in elderly. This activity was carried out in Sanga-Sanga District, Kutai Kartanegara Regency, East Kalimantan Province. With 60 elderly participants. Activities in the form of health screening for the elderly include blood pressure check, cholesterol level, uric acid level check and Personal Prevention Check Up (PPCU) followed by counseling how to prevent and control the risk of degenerative diseases that can be implemented by the elderly. The results showed that the highest risk of the health problems was the risk of nerve function, and the blood circulation disorders (60.7%). Therefore, knowledge regarding efforts to prevent and control the risk of degenerative disease is very important, especially in elderly.